Socialization of Introduction to Good and Correct Indonesian Through Reading Interest in Elementary School Students - Subakti, Hani (Penerbit dan Percetakan CV.Picmotiv, 2023)
Today, with advances in education and technology, extra skills are needed in order to continue to exist in society. One of the skills that every human being must possess today is language skills. The role of language is needed to master education, technology, communication, and when interacting directly. The focus of this community service activity is to develop the ability to read and study interest in elementary school students who are in Karang Anyar Village, Sungai Kunjang District, Samarinda City. The goal to be achieved is to increase the learning interest of elementary school students and improve language skills (soft skills). The results achieved are (1) elementary school students understand more about the importance of learning languages ​​since childhood, (2) elementary school students become familiar with the use of language, (3) elementary school students have readiness to enter association with various languages ​​and cultures. It is hoped that elementary school students will be able to communicate properly and correctly. This is because the foundation has been given from an early age to the introduction of good and correct Indonesian.